Study on the inverse problem of thin slab continuous casting mold based on fluid-solid coupled heat transfer - Yuxiao Fu; Guo Yuan; Guodong Wang; Qijia Mao (Case Studies in Thermal Engineering, 2024)
The thin slab continuous casting (TSCC) process employs a funnel-shaped mold, introducing increased complexity to both the structure and heat transfer of the mold, as well as the cooling water channels. This paper presents a three-dimensional fluid-solid coupled model for calculating the heat flux in a thin slab mold. The model is calculated and validated based on temperature data collected from molds and cooling water in the plant. The results show that the deviations of the wide face average heat flux and cooling water temperature difference from the measured values are 3.49 % and 1.1 %, respectively, demonstrating good agreement. Moreover, the influence of the thin slab mold geometry on heat transfer is explored. The heat flux values calculated in this model are approximately 13 % lower than those in the simplified model in the upper part of the original funnel area, and 2–7% lower in the lower part. Therefore, this model reflects the heat flux's three-dimensional characteristics of the funnel-shaped mold, offering a novel approach to calculating the heat flux of the thin slab mold.